1999
DOI: 10.1034/j.1600-051x.1999.t01-4-261101.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen metabolism in response to oestradiol‐17b and progesterone in human gingival fibroblasts (HGF) in culture

Abstract: The modulation of androgen metabolism by oestrogen and progesterone in HGF has been investigated, to elucidate hormone modulatory mechanisms, in periodontal disease presentation and healing responses. Duplicate incubations of HGF were performed in Eagle's MEM for 24 h with either 14C-testosterone/14C-4-androstenedione as substrate and serial concentrations of oestradiol-17beta, or progesterone (0.01-50 microg/ml). The effect of the anti- oestrogen tamoxifen on the action of oestradiol in HGF was also investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Effects of estrogen in the Periodontium increased amount of plaque with no increase of gingival inflammation inhibit proinflammatory cytokines release by human marrow cells (Gordon et al 2001) reduce T-cell-mediated inflammation (Josefsson et al 1992) suppress leukocyte production from the bone marrow (Josefsson et al 1992, Cheleuitte et al 1998 inhibit PMN chemotaxis (Ito et al 1995) stimulate PMN phagocytosis (Hofmann et al 1986) Table 2. Effects of progesterone in the periodontium increase production of prostaglandins (self-limiting process) (ElAttar 1976b, Smith et al 1986 increase polymorphonuclear leukocytes and PGE2 in the GCF reduce glucocorticoid anti-inflammatory effect (Feldman et al 1975, Chen et al 1977 altered collagen and noncollageneous protein synthesis (Willershausen et al 1991) alter PDL fibroblast metabolism (Nanba et al 1989b, Sooriyamoorthy & Gower 1989b, Tilakaratne & Soory 1999a increase vascular permeability (Abraham-Inpijn et al 1996) were positively correlated with free testosterone index and free estradiol index. They concluded that age as well as androgen and estrogen status are significant positive determinants, whereas parathyroid hormone (PTH) is a negative determinant of OPG serum levels in men (Szulc et al 2001).…”
Section: Androgens (Testosterone)mentioning
confidence: 99%
“…Effects of estrogen in the Periodontium increased amount of plaque with no increase of gingival inflammation inhibit proinflammatory cytokines release by human marrow cells (Gordon et al 2001) reduce T-cell-mediated inflammation (Josefsson et al 1992) suppress leukocyte production from the bone marrow (Josefsson et al 1992, Cheleuitte et al 1998 inhibit PMN chemotaxis (Ito et al 1995) stimulate PMN phagocytosis (Hofmann et al 1986) Table 2. Effects of progesterone in the periodontium increase production of prostaglandins (self-limiting process) (ElAttar 1976b, Smith et al 1986 increase polymorphonuclear leukocytes and PGE2 in the GCF reduce glucocorticoid anti-inflammatory effect (Feldman et al 1975, Chen et al 1977 altered collagen and noncollageneous protein synthesis (Willershausen et al 1991) alter PDL fibroblast metabolism (Nanba et al 1989b, Sooriyamoorthy & Gower 1989b, Tilakaratne & Soory 1999a increase vascular permeability (Abraham-Inpijn et al 1996) were positively correlated with free testosterone index and free estradiol index. They concluded that age as well as androgen and estrogen status are significant positive determinants, whereas parathyroid hormone (PTH) is a negative determinant of OPG serum levels in men (Szulc et al 2001).…”
Section: Androgens (Testosterone)mentioning
confidence: 99%
“…In addition, castration prevents calcium channel blocker-induced gingival overgrowth in beagle dogs (11). Although the molecular basis of these interactions remains poorly understood, Parkar et al (36) have shown, using semiquantitative reverse transcriptase-polymerase chain reactions (RT-PCR), that the androgen receptors but not the estrogen receptors are expressed by gingival fibroblasts, and that sex hormones influence the metabolism of fibroblasts derived from periodontal tissues (31,46). Moreover, recent studies have documented that the expression and production of interleukin-6 (IL-6) is downregulated by dihydrotestosterone, a potent metabolite resulting from metabolism of testosterone (15,35).…”
mentioning
confidence: 99%
“…Effective stimulatory/inhibitory concentrations of phenytoin, oestradiol and tamoxifen were established previously. It was 1 μ g/ml for each of phenytoin (Soory & Suchak 2001), oestradiol (Tilakaratne & Soory 1999) and tamoxifen (Tilakaratne & Soory 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Androgens and oestrogen have been shown to influence remodelling of the mandibular condyl in growing mice (Fujita et al 2001). Specific inhibition of androgen 5 α ‐reductase by the inhibitor finasteride in HGF (Soory & Virdi 1998) is suggestive of androgen target tissue activity in gingivae, which may be modulated by oestradiol (Tilakaratne & Soory 1999).…”
mentioning
confidence: 99%